Mental health among pregnant women under public health interventions during COVID-19 outbreak in Wuhan, China. (July 2021) - Xu, Ke; Zhang, Ya; Zhang, Yuanyuan; Xu, Qiao; Lv, Lan; Zhang, Jianduan
Highlights: Majority of pregnant women in wuhan developed psychological symptoms during the epidemic. Severe health-concerns and poor hygienic practices were negatively associated with maternal mental health. The anxiety level and sleep quality were better among those investigated during city reopening than that of city lockdown. Abstract: Coronavirus disease 2019 (COVID-19) has become a pandemic. As the first city struck by the COVID-19 outbreak, Wuhan had implemented unprecedented public health interventions. The mental health of pregnant women during these anti-epidemic controls remains unknown. A total of 274 pregnant women living in Wuhan during the COVID-19 outbreak took part in our investigation online. The data on mental health conditions were evaluated using Edinburgh Postnatal Depression Scale (EPDS), Self-Rating Anxiety Scale (SAS), Chinese Perceived Stress Scale (CPSS), and Pittsburgh Sleep Quality Index (PSQI). We also collected the information on physical health status and precautionary measures against COVID-19. The prevalence of depression, anxiety, stress, and poor sleep quality was 16.1%, 13.9%, 42.7%, 37.6%, respectively. Comparing to SAS, PSQI score in pregnant women who participated in the survey after April 8 (date of Wuhan reopening), those data collected before April 8 were significantly higher. High levels of stress, severe health concerns over the fetus, and poor hygienic practices were negatively associated with mental health conditions. In conclusion, a large proportion of pregnant women reported psychological symptoms during the epidemic, which negatively related to the severe health concerns over fetus and poor hygienic practices. More psychological support during the epidemic would promote maternal mental well-being.